2019
DOI: 10.1007/s10792-019-01174-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between allergic conjunctivitis and provisional tic disorder in children

Abstract: Background Allergic diseases are associated with a higher risk of Tourette's syndrome (TS). Provisional tic disorder (PTD) and eye blinking are often reported as the initial symptoms both in TS and in allergic conjunctivitis (AC). Objective To investigate the association between AC and PTD in children of 4-10 years of age in southwest China. Methods This case-control study was carried out at the Children's Hospital of Chongqing Medical University between January 2016 and June 2017. Age-and gender-matched child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…A fascinating study was driven by the clinical observation that blinking tics, a common first symptom of tic disorder, are often mistaken for allergic conjunctivitis (AC) by families and primary care physicians. A group in southwest China studied 70 children with provisional tic disorder (PTD) and 70 tic-free controls and found that AC was more than 4 times more common in PTD (74%) than controls (17%) (Chen et al 2020). They showed it could not all be symptom confusion, as quantitative measures of dry eyes and allergic responses to a skin prick test were also about four times more common in patients with PTD.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…A fascinating study was driven by the clinical observation that blinking tics, a common first symptom of tic disorder, are often mistaken for allergic conjunctivitis (AC) by families and primary care physicians. A group in southwest China studied 70 children with provisional tic disorder (PTD) and 70 tic-free controls and found that AC was more than 4 times more common in PTD (74%) than controls (17%) (Chen et al 2020). They showed it could not all be symptom confusion, as quantitative measures of dry eyes and allergic responses to a skin prick test were also about four times more common in patients with PTD.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…Both allergic and autoimmune diseases may arise from an impairment of the immune tolerance process. Clinical reports that linked allergic diseases to TS were based on population-based studies [44,45]. By using the National Health Insurance research database in Taiwan, Chang et al [44] found that TS is associated with common allergic diseases, including rhinitis, asthma, dermatitis, and allergic conjunctivitis.…”
Section: Immune Dysregulation In Tsmentioning
confidence: 99%
“…Allergic disease has become a major burden in the modern society of China due to a recent rise in its prevalence. Recent studies have reported that children with TD often present eczema, allergic rhinitis, allergic conjunctivitis, asthma, or other allergic diseases 13-15. Therefore, the relationship between TD and allergic diseases has gained attention among scientists and requires further study.…”
Section: Introductionmentioning
confidence: 99%